Simulasi Jaringan Drainase Kawasan Desa Lubuk Suli Kec. Depati VII Kabupaten Kerinci Menggunakan Program EPA SWMM Versi 5.1 - Putri, Ade Kurnia; Rahmawati, Devit; Nasution, Ari Endra (Jurnal Talenta Sipil, 2024)
One of the areas in Kerinci Regency that is often hit by floods is Lubuk Suli Village.  Flooding was caused by overflowing water from the Batang Marao river. The main objective of this research is to provide information to the relevant government about good drainage for the Lubuk Suli Village Area using existing data and planning data by simulating the capability of the Drainage Network for the Lubuk Suli Village Area using the EPA SWMM 5.1 program. The data used in this research are land use maps to determine the percentage of impervious area, rainfall data and drainage channel dimension data in the area. The rain data series used is hourly rain data. Due to the absence of hourly rainfall data at the rain station at the research location, hourly rainfall distribution was determined by changing the Intensity-Duration-Frequency (IDF) curve for a 5 year return period into a planned rainfall hyetograph using the Alternating Block Method (ABM). After all parameters have been input into EPA SWMM 5.1. Simulation can be done. The simulation quality is quite good if the continuity error for surface runoff and flow tracing is > 10%. The simulation carried out in this research is divided into 2 scenarios, namely with existing data and additional storage. From the simulation results, it was found that in the 2 scenarios, the number of flood points in the simulation for scenario 1 was 6 points and in scenario 2 there were 5 points. This shows that the drainage planning design for the Lubuk Suli Village area has not been able to overcome the existing drainage load in the area.